Non-sedative Antihistamines: Assessment of Efficacy Based on Total Nasal Symptom Score in Patient with Allergic Rhinitis. (KYAMC Journal, 2022)
Background: Allergic rhinitis is a common and chronic immunoglobulin E–mediated respiratory disorder following allergen exposure that can affect the quality of life and work activities. Antihistamine should be prescribed for the relief of persistent allergic symptoms & advised to avoid known allergens also.Objectives: The objective of the study is to assess the efficacy of non-sedating antihistamines in the treatment of allergic rhinitis based on the total nasal symptom score.Materials and Methods: This is a prospective study of patients with clinically diagnosed allergic rhinitis following inclusion & exclusion criteria at the study center. Patients’ demographic profiles, symptoms and signs were obtained using a specially designed form. The symptoms were scored from baseline to end of treatment by using nasal symptom scoring protocol. The data were collated and analyzed using Microsoft excel & SPSS Version 17 statistical software.Results: Recruited 360 patients with allergic rhinitis, 96.66% presented with running nose as the chief complaint. A large number of patients have total nasal symptom scores of above 9 (n =170; 47.22%), whereas few (n = 42; 11.66%) had symptom scores of below 6 at a baseline level. Upon treatment with rupatadine, a significant reduction of TNSS (p< 0.05) was found from baseline over the 14-day treatment period. The incidence of adverse effects (fatigue 1.3%, headache 2.7%) was found to be less in the rupatadine group.Conclusion: non-sedative antihistamines effectively control persistent allergic rhinitis, where rupatadine is a drug of choice due to its better efficacy and having a low incidence of side effects.KYAMC Journal. 2022;12(04): 231-236